2013
DOI: 10.2172/1162370
|View full text |Cite
|
Sign up to set email alerts
|

Technical Needs for Prototypic Prognostic Technique Demonstration for Advanced Small Modular Reactor Passive Components

Abstract: A key national energy priority to promote energy security is sustainable nuclear power. Nuclear energy currently contributes approximately 20% of baseload electrical needs in the United States and is considered a reliable generation source to meet future electricity needs. Advanced small modular reactors (AdvSMRs) using non-light-water reactor coolants such as liquid metal, helium, or liquid salt are promising mid-to long-term options being explored for added functionality and affordability in future reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 183 publications
2
40
0
Order By: Relevance
“…Details of advanced reactor concepts that are likely to be adapted for AdvSMR concepts are available in the previous report in this series (Coble et al 2013). Additional background on other advanced reactor concepts and operational experience are available in the report on prototypic prognostic techniques for AdvSMRs passive components (Meyer et al 2013a).…”
Section: Advsmr Oandm Conceptsmentioning
confidence: 99%
“…Details of advanced reactor concepts that are likely to be adapted for AdvSMR concepts are available in the previous report in this series (Coble et al 2013). Additional background on other advanced reactor concepts and operational experience are available in the report on prototypic prognostic techniques for AdvSMRs passive components (Meyer et al 2013a).…”
Section: Advsmr Oandm Conceptsmentioning
confidence: 99%
“…The condition indicator is then projected to future times using appropriate prognostic algorithms (Coble et al 2012;Meyer et al 2013), and estimate POF distributions for each key SSC at some point in the future. These estimated POF distributions are used by the ERM to provide a more accurate assessment of the dynamic risk.…”
Section: Enhanced Risk Monitorsmentioning
confidence: 99%
“…Many approaches to estimating the failure probabilities at future times are available for nuclear power system components (Coble et al 2012;Coble et al 2013;Meyer et al 2013). A common approach involves characterization of the expected lifetime of an average system or component operating in an average environment, under average usage conditions.…”
Section: Estimating Failure Probabilitiesmentioning
confidence: 99%
“…Some key factors of AdvSMRs that will impact PHM systems for passive components include i) the operating environment, ii) O&M, iii) concepts of operation, iv) materials degradation performance, v) past operating experiences, vi) balance-of-plant, and vii) refueling intervals. A brief discussion of these factors as they relate to AdvSMRs is provided in [3]. For instance, one of the factors of AdvSMRs that will influence the implementation of PHM systems for passive components is the coupling of AdvSMR systems to multiple product streams (illustrated in Fig.…”
Section: Requirements Analysismentioning
confidence: 99%
“…This paper provides a summary of a recent technical needs and research gap assessment documented in a technical report [3]. Research gaps and technical needs are identified based on a requirements analysis for PHM of AdvSMR passive components and a PHM state-of-the-art assessment relevant to AdvSMR passive components.…”
Section: Introductionmentioning
confidence: 99%